Hankel convolution of generalized functions - I. MARRERO; J.J. BETANCOR (Rendiconti di Matematica e delle Sue Applicazioni, 1995)
In this paper the Hankel convolution introduced by Hirschman and Cholewinski is defined on a space of generalized functions wider than that considered by Sousa-Pinto. Algebraic and topological properties of this generalized Hankel convolution are established.